2021
DOI: 10.3389/fphar.2021.594793
|View full text |Cite
|
Sign up to set email alerts
|

Circ_CLASP2 Regulates High Glucose-Induced Dysfunction of Human Endothelial Cells Through Targeting miR-140-5p/FBXW7 Axis

Abstract: Hyperglycemia exposure results in the dysfunction of endothelial cells (ECs) and the development of diabetic complications. Circular RNAs (circRNAs) have been demonstrated to play critical roles in EC dysfunction. The current study aimed to explore the role and mechanism of circRNA CLIP–associating protein 2 (circ_CLASP2, hsa_circ_0064772) on HG-induced dysfunction in human umbilical vein endothelial cells (HUVECs). Quantitative real-time polymerase chain reaction (qRT-PCR) was used to assess the levels of cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In contrast, it has been demonstrated that circ_CLASP2 is decreased in HG-induced HUVECs. Circ_CLASP2 protects HUVECs against hyperglycemia dysfunction by regulating the miR-140-5p/FBXW7 pathway ( Zhang et al, 2021b ).…”
Section: The Role Of Circrnas In Diabetic Complicationsmentioning
confidence: 99%
“…In contrast, it has been demonstrated that circ_CLASP2 is decreased in HG-induced HUVECs. Circ_CLASP2 protects HUVECs against hyperglycemia dysfunction by regulating the miR-140-5p/FBXW7 pathway ( Zhang et al, 2021b ).…”
Section: The Role Of Circrnas In Diabetic Complicationsmentioning
confidence: 99%
“…Parallel to lncRNAs, most circRNAs regulate FBXW7 as miRNA "sponges". For instance, hsa_circ_11780 (93), circFBXW4 (94), Hsa_circ_001988 (95), circ_CLASP2 (96), circBRAF (97), circ_0000094 (98), hsa_circ_0001306 (99), hsa_circ_0022742 (100), circPSD3 (101), and circKL (102) were confirmed to sponge different miRNAs to impact the expression of FBXW7, respectively. Intriguingly, although the majority of circRNAs are deemed unable to code proteins as non-coding RNAs, a special circRNA associated with FBXW7 has been confirmed the function of coding protein.…”
Section: Circular Rna Regulation Of Fbxw7mentioning
confidence: 94%
“…Glucose concentrations between 20 to 30 mmol/l have been used to mimic high-glucose conditions in previous studies. [25][26][27][28] Our experiments were conducted in cells treated by NG (5 mmol/l), HG (20 mmol/l), HG (30 mmol/l) and mannitol as an osmotic control for more rigorous study design and careful conclusions. We labeled HUVECderived exosomes with DiD fluorescent probes and uptake of the labeled exosomes by HTR-8a/SVneo cells was certified by immuno-fluorescent imaging.…”
Section: Htr-8a Cells Treated By Hg-huvec-exo Demonstrated Cell Damag...mentioning
confidence: 99%